THE EFFECT OF LIQUIDITY, LEVERAGE, AND PROFITABILITY RATIO ON STOCK PRICES - Selaksa Dian Sukma; Suhendro Suhendro; Purnama Siddi (Universitas Slamet Riyadi, 2020)
The purposes of this study is to test and analyze the influence of liquidity (Current Ratio), leverage (Quick Ratio, Debt to Equity ratio), profitability (Return on Asset, Return on Equity) and stock prices on food and beverage companies listed in Indonesia Stock Exchange 2016-2018 period. The dependent variable of the study is stock price, liquidity (Current Ratio), leverage (Quick Ratio, Debt to Equity Ratio), profitability (Return on Assets, Return on Equity). The population includes 18 companies and 10 research sample companies according to criteria specified and during the period 2016-2018, making a total of 30 observation data according to the criteria. The sampling technique used purposive sampling. methods of data analysis using panel data regression, F test shows that the test results of the partial test (t test) showed variable profitability (Return on Assets and Return on Equity) effect on the stock price, the variable liquidity (Current Ratio), leverage (Quick ratio, and Debt to Equity Ratio) no significant effect on the price on stock.